Back to the rough ground: Textual, oral and enactive meaning in comparative political theory. (July 2021) - Rollo, Toby
The emerging field of comparative political theory (CPT) seeks to expand our understanding of politics through intercultural dialogues between diverse systems of political thought. CPT acknowledges diverse modes of political understanding, yet the field is still methodologically focused on textual forms of political practice and learning. I argue that the privileging of political literature in CPT has been inherited from orthodox political theory and the history of political thought and that the prioritizing of text over oral and enactive practices places constraints on intercultural dialogue. First, methodological focus on texts inhibits dialogue with Indigenous traditions that do not prioritize text in the same way or to the same extent in the reproduction of political culture. Second, the incorporation of oral traditions tends to conflate orality with text in ways that obfuscate the contribution of enactive performance. One result of these methodological oversights is that CPT risks recapitulating some of the historical exclusionary logics that it seeks to overcome.